Myostatin Gene as a Genetic Marker for Growth and Carcass Traits in Beef Cattle - Peni Wahyu Prihandini; D N H Hariyono; Y A Tribudi (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2021)
Growth and carcass traits are of economic importances in livestock breeding, because they affect the profitability of animal production. The phenotypic expression of these traits is controlled by multiple genes (polygenes), such as myostatin (MSTN) gene. This paper aims to discuss the expression, polymorphism and potential application of MSTN gene as a marker-assisted selection (MAS) for growth and carcass traits in beef cattle based on data from published studies. MSTN gene or known as growth and differentiation factor 8 (GDF8) is a member of the transforming growth factor-β (TGF-β) superfamily, which acts as a negative regulator of skeletal muscle mass deposition. Several published studies showed that mutations in the MSTN gene can inhibit the activation of myostatin, which leads to an increased muscle mass (hypertrophy). Several MSTN gene polymorphisms were reported to be associated with growth and carcass traits in local cattle in several countries, including Indonesia, namely Bali cattle. Based on several assumptions: 1) there is MTSN gene polymorphisms in a population, 2) there is a significant association between MSTN gene polymorphisms and growth and carcass traits, as reported in several beef cattle populations and 3) those cattle with superior genotype have better growth performances, we expect that there will be improvement in growth performances in the future if those cattle are selected. Understanding MSTN gene polymorphisms would be useful to make strategies for the genetic improvement for growth and carcass traits of local cattle.